Color Stability of Different Aesthetic Resin Composite Materials: A Digital Image Analysis - Shatha Abdul-Kareem1, Ahmed G. Al-Maroof 2, Noor H. Fadhil3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
This study aimed to evaluate and compare the color stability of three commercially available resins composites after exposure to different staining solutions using digital image analysis.A total of ninety-disc shape specimens of a microhybrid composite (Amelogen plus), ultrafine hybrid composite (Essentia), and nanohybrid composite (Beautifil II) were produced in Teflon mould (n=30/ resin composite type). Specimens of each resin composite were then divided into 5 subgroups (n=6/subgroup) and immersed in 200 ml of Pepsi, orange juice, tea, coffee and artificial saliva (control group), respectively. Digital images of the specimens were taken before (baseline) and after 28 days immersion against a black and white background. Adobe Photoshop CS6, Ver.13.0.1 graphic program (AdobeSystems Inc., San Jose, CA, USA) was used to analyze the digital images and calculate the change in color (?E). Data were submitted to statistical analysis using one-way ANOVA and Tukey Posthoc test at a significance level of p<0.05. This study concluded that all resin composites exhibited color changes after immersion in all staining solutions. However, Amelogene Plus showed better resistance to staining compared to Beautifil II and Essentia.